Peran Sistem Informasi Manajemen Desa Sebagai Instrumen Penguatan Transparansi Dan Akuntabilitas Pemerintahan Desa - Fahri; Muhammad Irwan Padli Nasution (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
In the current digital era, village governments in Indonesia are faced with challenges to improve transparency and accountability in managing resources and delivering public services. Village Management Information Systems (Village MIS) have emerged as important instruments to support these objectives. This study aims to analyze the role of Village MIS in strengthening transparency and accountability in village governance, with a focus on how these systems facilitate data management, communication, and better decision-making processes. Using a descriptive qualitative approach, this study collects data through a literature review of various relevant sources, including academic journals, books, and government regulations. The results indicate that Village MIS plays a significant role in enhancing transparency by providing information that is easily accessible to the public, as well as strengthening accountability by enabling accurate reporting and monitoring of village government activities. However, the implementation of Village MIS still faces several challenges, such as limited technological infrastructure, insufficient human resource skills, and resistance from village officials. This study recommends strengthening the capacity of village apparatus through training programs and investments in information technology to optimize the role of Village MIS. Overall, Village MIS functions not only as a technical tool but also as a means to build public trust in village governance, thereby supporting the achievement of good governance at the village level.